(untitled) (Atlas Journal of Biology, 2019)
The present study was conducted at the farm of The Rice Research and Training Center, (RRTC), Sakha, Kafr El-Sheikh, Egypt, during the 2016, 2017 and 2018 seasons. Six rice cultivars (Oryza sativa L.) that differed in their grain quality characters were used as parents to produce six generations of three crosses of rice namely ‘Giza178’×’EgyptianYasmine’, ‘Giza177’×’UPR82-1-7’ and ‘IET1444’×’Pusa Basmati1’. Generation mean analysis was used to estimate types of gene actions, heterosis, inbreeding depression, heritability and genetic advances for milling%, grain dimensions and cooking and eating characters. The results indicated that the scaling test was significant for one scale in all the crosses for all the traits, indicating an inadequacy of the simple additive dominance model. Segregation analysis indicated partial dominance for grain quality characters for almost crosses except gel consistency and amylose content percentage. This suggested over dominance for most traits in most crosses. Moreover, evaluation of genetic parameters indicated the importance of additive gene effects. That were significant and positive in the inheritance of grain quality characters for the three crosses. Exceptions were grain length and grain shape which were significant and negative. Different types of gene action were detected, varying by the characters and the crosses under study. Epistasis was observed among the crosses. Heritability estimates for milling and eating and cooking quality were low to moderate indicating that selection exercised in late generations may be effective. Heritability estimates for grain dimensions were high, suggesting that selection in early generation will be effective in future.